A study of the Factors affecting Seepage and Methods for Evaluating Losses due to Seepage in Small irrigation Channels.
Seepage has beefi defined as the movement of water into or out of the ground. Acc or ding to (’seepage is the perco- Meinzer, (l) lation through the surface of the lithosphere or through the walls of large opening in it, such as caves or artificial excavations". Perco- lation occurs through smal